The Analysis of German Separable Prefix Verbs in the Microsoft Natural Language Processing System - Gamon, Michael; Reutter, Tom (1997)
In this paper we present an analysis of separable prefixes in German within the Microsoft Natural Language Processing System. We illustrate a simple solution to the problem of separated prefixes in our augmented phrase structure grammar which uses binary syntactic rules. The solution is based on the treatment of separated prefixes as verbs. We discuss the semi-automatic generation of the necessary lexical entries and the syntactic analysis based on these entries. We show that under our approach only one new rule needs to be added to our grammar to accommodate the facts, and that only small modifications to existing rules are necessary.